The influence on the quality of life those who practice gymnastics at work - Macedo, Douglas Henrique da Silva; Gonçalves, Ricardo (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Educação Física, 2024)
In this study, it was verified what the impacts that Gymnastics Labor brings to the workers and to other people who also practice, also trying to demonstrate how it is important for the population that performs this gymnastics as well as the benefits that they can bring, caused by repetitive movements, aiming to reduce stresses and pain by the muscular or skeletal body. In this context, we sought to bring bibliographic studies of the existing literature and on labor gymnastics, as it influences the quality of life and how it can contribute to a healthier life by removing possible complications from the daily routine of the general population. The methodology used was to carry out a bibliographic review, where scientific articles searched through the following databases, Google Scholar and Scielo, will be consulted, selecting articles and magazines between the years 2016 and 2023. There are several studies demonstrating that GL does bring benefits for the worker, then it should be practiced whenever possible, since it will contribute in the future, also providing for the quality of life of people, making them healthier.